2023
DOI: 10.3390/met13071152
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Key Factors Affecting the Wear Performance of Medium Manganese Steels

Abstract: In recent years, medium manganese steels (MMSs) have garnered increased attention and interest due to their relatively low cost and superior combination properties compared to other steels. In particular, MMSs have been recognised as ideal wear-resistant materials employed in the mining industry. However, the studies on their wear performance have a lack of systematic documentation. This review provides an extensive overview of recent advances in the wear performance of MMSs, starting from discussions on appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…It should be noted that recently mediummanganese steels have attracted increased attention due to their relatively low cost (reduced manganese content compared to 110G13L) and sufficient physical and mechanical properties for the relevant conditions [13,14]. And in [15] it was found that at low and medium loads, the wear resistance of austenitic medium-manganese steels is even higher than that of high-manganese steels.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that recently mediummanganese steels have attracted increased attention due to their relatively low cost (reduced manganese content compared to 110G13L) and sufficient physical and mechanical properties for the relevant conditions [13,14]. And in [15] it was found that at low and medium loads, the wear resistance of austenitic medium-manganese steels is even higher than that of high-manganese steels.…”
Section: Resultsmentioning
confidence: 99%